Determinacy and learnability of monetary policy rules in small open economies - Gonzalo Llosa; Vicente Tuesta (Inter-American Development Bank, Research Department, 2006)
This paper evaluates under which conditions different Taylor-type rules lead to determinacy and expectational stability (E-stability) of rational expectations equilibrium in a simple 'New Keynesian' small open economy model, developed by Gali and Monacelli (2005). In particular, we extend the Bullard and Mitra (2002) results of determinacy and E-stability in a closed economy to this small open economy framework. Our results highlight an important link between the Taylor principle and both determinacy and learnability of equilibrium in small open economies. More importantly, the degree of openness coupled with the nature of the policy rule adopted by the monetary authorities might change this link in important ways. A key finding is that, contrary to Bullard and Mitra, expectations-based rules that involve the CPI and/or the nominal exchange rate limit the region of E-stability and the Taylor Principle does not guarantee Estability. We also show that some forms of managed exchange rate rules can help to alleviate problems of both indeterminacy and expectational instability, yet these rules might not be desirable since they promote greater volatility in the economy.
Keywords: E4; E5; F31; F41; 330; Learning; Indeterminacy; Monetary Policy Rules; Open Economy; Geldpolitik; Kleines-offenes-Land; Taylor-Regel; Rationales Verhalten; Neukeynesianische Makroökonomik; Theorie